The impact of social media visual features on acceptance of meat substitute. (November 2022) - Septianto, Felix; Kemper, Joya A; Quang, Huy P; Li, Shuge; Kwon, Junbum
There is a growing demand for meat substitutes among consumers, given that excessive meat consumption is associated with negative consequences for personal health and the environment. However, the market shares of such meat substitutes remain low, thus highlighting the need to further investigate how to increase consumer acceptance of meat substitutes. The present research investigates social media data of plant-based meat brands and explores how visual features could lead to a high number of likes, which is a numerical representation of social acceptance. The findings of this research show that social media posts with warm color, vertical symmetry, and horizontal symmetry receive a higher number of likes. Further, there is a joint effect between warm color and vertical symmetry, such that vertical symmetry would strengthen the positive effect of warm color on the number of likes. These findings offer a more nuanced understanding of how to increase consumer acceptance of meat substitutes and how to promote plant-based meat brands in social media.